2018
DOI: 10.1021/acs.analchem.7b03948
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Proteoform Analysis of Histones H3 and H4 with a Simplified Middle-Down Proteomics Method

Abstract: Dynamic post-translational modifications of histones regulate transcriptional gene expression in eukaryotes. Unique combinations of modifications, almost exclusively displayed at the flexible N-terminal tails on histones, create distributions of proteoforms that need to be characterized in order to understand the complexity of gene regulation and how aberrant modification patterns influence disease. Although mass spectrometry is a preferred method for the analysis of histone modifications, information is lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Samples were desalted using C18 ZipTips prior to nano liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis. All histone digests were analyzed on an Orbitrap Velos mass spectrometer coupled to an EASY-nLC 1000 system (Thermo Fisher Scientific, Bremen, Germany) equipped with a Nanospray Flex ion source as it has been described elsewhere 64 . The flow rate was set to 300 nL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were desalted using C18 ZipTips prior to nano liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis. All histone digests were analyzed on an Orbitrap Velos mass spectrometer coupled to an EASY-nLC 1000 system (Thermo Fisher Scientific, Bremen, Germany) equipped with a Nanospray Flex ion source as it has been described elsewhere 64 . The flow rate was set to 300 nL/min.…”
Section: Methodsmentioning
confidence: 99%
“…used an alternative protease, Neprosin, to generate H3 peptide 1-38 AA as the most abundant H3 digestion product which allows better retention and dispersion than H3 N-tail 1-50 AA on reversed-phase chromatography (23). Janssen et al used porous graphitic carbon (PGC) as a novel stationary phase and achieved simultaneous bottom-up and middle-down histone analysis using the same reversed-phase buffer setup (31).…”
Section: Middle-down Proteomicsmentioning
confidence: 99%
“…76,184 Very recently, Schräder et al have reported MD strategy by using neprosin, a novel propylendoprotease for getting the middle-range sized peptides to characterize the H3 and H4 histones of HeLa S3 cells. 267 It needs to be noted that BU approach may not be suitable to study histones, especially their PTMs. 77,268 This is because N-terminal tails of histones are rich in lysine and arginine residues and therefore, very short length peptides would be produced upon carrying out trypsin digestion.…”
Section: 1 Ptms On Histonesmentioning
confidence: 99%